Some problems of testing pupils in English as a foreign language: Case of Kananga secondary schools - David LUMBALA (Diversitate si Identitate Culturala in Europa)
Knowing a language is being able to use it in the daily speech LADO (1961: 17). This means, being capable of listening. Reading and writing. These four skills should be taught and tested by the teacher in order to know if learners have mastered lessons previously taught or exchange their thoughts, feelings and ideas.